MOTIVASI BELAJAR DALAM PENDIDIKAN ANDRAGOGI PERSPEKTIF PENDIDIKAN ISLAM (Studi Analisis Teori Kebutuhan As Syathibi) - Nur Ali Subhan (Program Studi Pendidikan Agama Islam UNU Purwokerto, 2023)
Abstract Motivation to learn is the main key for students in undergoing the educational process. Students who have motivation to learn will devote all their abilities to achieving learning goals. In andaragogy education, students' learning motivation is different from other types of education. Adult education has more complex educational goals so that the motivation required is realistic. This research aims to determine learning motivation in andargogical education from an Islamic perspective by examining As Syathibi theory of needs. This type of research is a study of a character's thoughts using library research methods and using a qualitative descriptive approach. The data collection method uses the documentation method with content analysis techniques (Content Analysis) to analyze message content and message management regarding the meaning contained in the sources used and has the unction of revealing hidden symbolic meanings. Based on the research conducted, the results show that there are three levels of Imam As Syathibi perspective needs which motivate learning in andragogy education; namely dharuriyat needs, hajiyat needs and tahsiniyat needs. The first level, dharuriyat needs, is the level of primary needs which include hifzh al-din (maintaining religion), hifzh al-nafs (maintaining the soul), hifzh al-'aql (maintaining reason), hifzh al-nasl (maintaining offspring), and hifzh al-mal (guarding wealth).